Visualization of horizontal canal benign paroxysmal positional vertigo using 3DCT imaging and its assessment - Yamane, Hideo; Konishi, Kazuo; Anniko, Matti (Acta Oto-Laryngologica, 2021)
There have been no useful imaging methods to diagnose benign paroxysmal positional vertigo (BPPV), a common cause of vertigo, depending on the characteristic symptom. To visualize horizontal canal (HC) BPPV using 3DCT and assess its clinical usefulness. Ten BPPV patients were diagnosed with distinct BPPV, canalolithiasis, and cupulolithiasis of the HC (hc-BPPV, hc-BPPV-cu), which were definitely diagnosed on the basis of criteria of BPPV by the Barany Society and 10 healthy subjects without a history of dizziness were investigated using 3DCT with several different CT window values (CTWVs). The HCs of BPPV patients were clearly visualized and the luminal aspects showed differences among ears with cupulolithiasis, canalolithiasis and no symptoms healthy subjects. 3DCT images visualized the characteristic changes of the HC of patients with BPPV compared to healthy subjects. The HC images were coincident with the clinical condition of cupulolithiasis and canalolithiasis. This imaging technique is clinically useful for diagnosing, treating and assessing the prognosis of HC BPPV